A contribution to the theory of R&D investments - Domenico Buccella; Luciano Fanti; Luca Gori (Global Labor Organization (GLO), 2021)
This research contributes to the theory of cost-reducing R&D investments by offering a tractable three-stage non-cooperative Cournot duopoly game in which R&D-investing firms choose whether to disclose R&D-related information to the rival. Though in a noncooperative context firms have no incentive to unilaterally disclose information on their costreducing R&D activity to prevent the rival from freely appropriate it, this work shows that there is room for the government to design an optimal policy aimed at incentivising unilaterally each owner towards R&D disclosure. Under this welfare improving policy, sharing R&D-related information becomes a Pareto efficient Nash equilibrium strategy of selfish firms. These findings suggest that introducing public subsidies aimed at favouring R&D disclosure represents a win-win result, eliminating the so far established - and unpleasant for both firms and society - non-disclosing outcome.
Keywords: D43; L13; O31; 330; Cost-reducing innovation; Nash equilibrium; Government; Social welfare